2012
DOI: 10.1039/c2md20238g
|View full text |Cite
|
Sign up to set email alerts
|

A furoxan–amodiaquine hybrid as a potential therapeutic for three parasitic diseases

Abstract: Parasitic diseases continue to have a devastating impact on human populations worldwide. Lack of effective treatments, the high cost of existing ones, and frequent emergence of resistance to these agents provide a strong argument for the development of novel therapies. Here we report the results of a hybrid approach designed to obtain a dual acting molecule that would demonstrate activity against a variety of parasitic targets. The antimalarial drug amodiaquine has been covalently joined with a nitric oxide-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 27 publications
0
13
0
1
Order By: Relevance
“…Nitrosation of the cinnamic alcohol fragment in quinoline 87 followed by a four‐step functional group interconversion afforded hybrid 89 with satisfactory overall yield (Scheme ). Furoxan 89 displayed significant activity against the parasites P. falciparum , S. mansoni , and A. ceylanicum , which allows consideration of hybrid 89 as a drug candidate for the treatment of various parasitic diseases …”
Section: Synthesis No‐donor Properties and Pharmacological Activitmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrosation of the cinnamic alcohol fragment in quinoline 87 followed by a four‐step functional group interconversion afforded hybrid 89 with satisfactory overall yield (Scheme ). Furoxan 89 displayed significant activity against the parasites P. falciparum , S. mansoni , and A. ceylanicum , which allows consideration of hybrid 89 as a drug candidate for the treatment of various parasitic diseases …”
Section: Synthesis No‐donor Properties and Pharmacological Activitmentioning
confidence: 99%
“… Synthesis of furoxan‐based amodiaquine structural analogues . Reagents and conditions : a) NaNO 2 , AcOH, RT, 10 h, 57 %; b) TBSONHTs, DIAD, PPh 3 , THF, 55 °C, 72 h, 62 %; c) CsF, MeCN, RT, 30 min, 48 %; d) SOCl 2 , DMF, 0 °C, 10 min, 96 %; e) 4 m HCl, dioxane, MeOH, RT, 30 min, 98 %.…”
Section: Synthesis No‐donor Properties and Pharmacological Activitmentioning
confidence: 99%
“…[152] The regioisomeric furoxan 174 was obtained by thermal isomerization of 173 in toluene. The peptidomimetic scaffolds 177 were assembled by initial conversion of the azide to amine function via the Staudinger reduction.…”
Section: Case Studies Of Heterocyclic N-oxide Drugs and Emerging Bmentioning
confidence: 99%
“…[151] It has been shown that the quinine core common to amodiaquine and chloroquine possess activity against other parasitic diseases, most notably schistosomiasis. Thus, Mott and coworkers [152] applied the concept of drug hybridization in the development of a new therapy by combining the beneficial features of furoxans (known NO donor) and that of the quinine core (Figure 42). …”
Section: Case Studies Of Heterocyclic N-oxide Drugs and Emerging Bmentioning
confidence: 99%
“…), [7][8][9] including the 1,2,5-oxadiazole 2-oxides (furoxans) which are capable of exogenous NO release at the presence of thiol cofactors. 10,11 Furoxans comprise a valuable class of five-membered heterocycles and can serve as a privileged motif in medicinal and pharmaceutical chemistry owing to their significant biological activities, for example neuroprotective and precognitive, 12 cytotoxic, 13,14 antihelmintic, 15 antibacterial 16 and fungicidal 17 , connected with the high capacity of furoxans to produce a large flux of NO. It was established that NO exerts a cytotoxic effect at high concentrations, while low levels of NO are potentially protective, particularly in the CNS.…”
Section: Introductionmentioning
confidence: 99%